Perspectives on Rodolfo Kusch’s philosophy: method, popular approach and indigenous people as questioning horizons in Latin American philosophy (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This paper analyses the work of Rodolfo Kusch remarking his main philosophical proposals through three correlated perspectives. The first perspective refers to phenomenology and culture. The second focuses on the influence of anthropology and the problem of symbols. The third posits a political-philosophical approximation. These perspectives operate interdependently as the background for Kusch‟s philosophy and allow us to introduce three “questioning horizons” related to the method, the popular and the indigenous as the central issues of his philosophical work. Thus, these “questioning horizons” build a platform to understand Kusch‟s philosophy and his contribution to the Latin American philosophy.
Keywords: Rodolfo Kusch; Latin American Philosophy; Method; Popular; Indigenous